The 2010 International Power Electronics Conference - ECCE ASIA - 2010
DOI: 10.1109/ipec.2010.5542008
|View full text |Cite
|
Sign up to set email alerts
|

Position-sensorless control method at low speed for permanent magnet synchronous motors using induced voltage caused by magnetic saturation

Abstract: A new position-sensorless method has been developed for a permanent magnet synchronous motor (PMSM) drive at low speed. This method utilizes the induced voltage caused by magnetic saturation of PMSM. The rotor position can be detected by using the open phase voltage of a conventional 120-degree commutation. No harmonic injection is needed. This paper discusses the principle of the proposed method and the experimental results.Index Terms--motor drive, PMSM, sensorless control, 120 degree commutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Sections IV and V explain simulation analysis with these methods. Figure 10 clarifies the principles underlying the estimation of initial rotor position [5], where voltage pulses were applied to PMSMs. Positive and negative currents were generated in each phase by these pulses.…”
Section: Es Timation Of Initial Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections IV and V explain simulation analysis with these methods. Figure 10 clarifies the principles underlying the estimation of initial rotor position [5], where voltage pulses were applied to PMSMs. Positive and negative currents were generated in each phase by these pulses.…”
Section: Es Timation Of Initial Positionmentioning
confidence: 99%
“…This indicated that the N-model was very useful for designing estimates of the initial position. A position sensorless method for non-salient PMSMs has previously been reported [5] and [6], where PMSM is driven by block commutation and open phase voltage is detected. The generated voltage in the open phase is called induced voltage caused by magnetic saturation (IVMS).…”
Section: Es Timation Of Initial Positionmentioning
confidence: 99%
“…Moreover, the DFC technique has been successfully used in several practical applications such as the identification of electrical and mechanical parameters of PMSMs [31] and the observation of the external load torque using state observation techniques in [32]. Besides this technique, another interesting approach was proposed by [33] that goes under the name of IVMS (induced voltage caused by magnetic saturation), that is capable of estimating the electrical rotor position by exciting two machine phases at a time and measuring the neutral point voltage. This first version of the technique was designed for brushless DC machines (BLDC), that are typically driven by means of block commutation (while Brushless AC Machines, BLAC, rely on sinusoidal commutation).…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the quality of such measurements, a Fast resettable integrator circuit (FRIC) was presented in [21][22][23]. Another interesting usage of the zero-sequence voltage for sensorless operation of PMSMs is reported, firstly, in [24], where the machine is operated by exciting two machine phases and by measuring the induced voltage caused by magnetic saturation (IVMS) allowing for the estimation of the rotor position. This technique presented the limitation of allowing only block-commutation so, in order to overcome this limitation, this technique was further developed and proposed in [25].…”
Section: Introductionmentioning
confidence: 99%